Intelligent RAM (IRAM): the industrial setting, applications, and architectures - Patterson, D.; Asanovic, K.; Brown, A.; Fromm, R.; Golbus, J.; Gribstad, B.; Keeton, K.; Kozyrakis, C.; Martin, D.; Perissakis, S.; Thomas, R.; Treuhaft, N.; et al. (Proceedings International Conference on Computer Design VLSI in Computers and Processors, 1997)
The goal of intelligent RAM (IRAM) is to design a cost-effective computer by designing a processor in a memory fabrication process, instead of in a conventional logic fabrication process, and include memory on-chip. To design a processor in a DRAM process one must learn about the business and culture of the DRAMs, which is quite different from microprocessors. The authors describe some of those differences and their current vision of IRAM applications, architectures, and implementations.